Structural brain signatures of frailty, defined as accumulation of self-reported health deficits in older adults - Gutiérrez-Zúñiga, Raquel; Davis, James R. C.; Ruddy, Kathy; De Looze, Céline; Carey, Daniel; Meaney, James; Kenny, Rose Anne; Knight, Silvin Paul; Romero-Ortuno, Roman (Frontiers in Aging Neuroscience, 2023)
Background: Frailty in older adults has been associated with reduced brain health. However, structural brain signatures of frailty remain understudied. Our aims were: 1) Explore associations between a frailty index (FI) and brain structure on magnetic resonance imaging (MRI); 2) identify the most important FI features driving the associations. Methods: We designed a cross-sectional observational study from a population-based study (The Irish Longitudinal Study on Ageing: TILDA). Participants aged ≥ 50 years who underwent the wave 3 MRI sub-study were included. We measured cortex, basal ganglia, and each of the Desikan-Killiany regional volumes. Age- and sex-adjusted correlations were performed with a 32 item self-reported FI that included conditions commonly tested for frailty in research and clinical settings. A graph theory analysis of the network composed by each FI item and cortex volume was performed. White matter fibre integrity was quantified using diffusion tensor imaging (DTI). Results: In 523 participants (mean age 69, 49% men), lower cortex and thalamic volumes were independently associated with higher FI. Sensory and functional difficulties, diabetes, polypharmacy, knee pain, and self-reported health were the main FI associations with cortex volume. In the network analysis, cortex volume had a modest influence within the frailty network. Regionally, higher FI was significantly associated with lower volumes in both orbitofrontal and temporal cortices. DTI analyses revealed inverse associations between the FI and the integrity of some association bundles. Conclusions: The FI used had a recognisable but scarce structural brain signature in this sample. Only some FI deficits were directly associated with cortex volume, suggesting scope for developing FIs that include metrics more specifically related with brain health in future aging neuroscience related studies.